317 Evaluating the Utility of the Fungal Stain in the Microbiology Laboratory. (11th January 2018) - Ma, Qiuping; Alby, Kevin; Glaser, Laurel
Abstract: Objectives: Requests for fungal stain (potassium hydroxide [KOH]-calcofluor stains) for fungal detection have significantly increased in our microbiology laboratory and demand significant laboratory effort. Here we evaluate the added benefit of fungal stain in detecting the presence of fungus in specimens concurrently examined by other methods. Methods: We calculated the positive rate of all fungal stains (n = 1, 752) performed between July and September 2016, and further characterized the 92 positive fungal stains performed between June and November 2016 in our microbiology laboratory. Conclusion: The positive rate of all fungal stains (n = 1, 752) was 2.7%. All of the 92 specimens with positive fungal stains were also submitted for fungal culture, and 96.7% were submitted for Gram stain and routine culture. Concurrent specimens from 55.4% of these cases were submitted for cytological and/or histopathological examinations most frequently from the respiratory tract (except for sputum) or surgically obtained tissue. We found that most of the specimens with positive fungal stain were also detected by other methods: 83.7% by fungal culture, 70.6% by cytological and/or histopathological examination, and 39.3% by Gram stain. In the specimens submitted for both fungal culture and either cytological or histopathological examination, the positive detection rate was 96.1% by both methods compared to 83.7% by fungal culture alone. Alternatively, Gram stain had no added benefit to fungal culture. A single case, from a maxillary sinus, was detected by fungal stain only but not any other method. Together, these findings demonstrate that if a specimen is submitted for both fungal culture and cytological and//or histopathological examination, fungal stain does not significantly increase detection rate. Performing fungal stains only on critical specimens or by physician request when the decreased time to detection could be clinically meaningful would reduce unnecessary and burdensome testing.